Evolutionary Responses of Drosophila melanogaster Under Chronic Malnutrition - Ahmad, Muhammad; Keebaugh, Erin S.; Tariq, Muhammad; Ja, William W. (Frontiers in Ecology and Evolution, 2018)
Drosophila species have successfully spread and adapted to diverse climates across the globe. For D. melanogaster, rotting vegetative matter provides the primary substrate for mating and oviposition, and also acts as a nutritional resource for developing larvae and adult flies. The transitory nature of decaying vegetation exposes D. melanogaster to rapidly changing nutrient availability. As evidenced by their successful global spread, flies are capable of dealing with fluctuating nutritional reserves within their respective ecological niches. Therefore, D. melanogaster populations might contain standing genetic variation to support survival during periods of nutrient scarcity. The natural history and genetic tractability of D. melanogaster make the fly an ideal model for studies on the genetic basis of resistance to nutritional stress. We review artificial selection studies on nutritionally-deprived D. melanogaster and summarize the phenotypic outcomes of selected animals. Many of the reported evolved traits phenocopy mutants of the nutrient-sensing PI3K/Akt pathway. Given that the PI3K/Akt pathway is also responsive to acute nutritional stress, the PI3K/Akt pathway might underlie traits evolved under chronic nutritional deprivation. Future studies that directly test for the genetic mechanisms driving evolutionary responses to nutritional stress will take advantage of the ease in manipulating fly nutrient availability in the laboratory.